2021
DOI: 10.1172/jci.insight.143626
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mapping of interstitial lung disease reveals a phenotypically distinct senescent basal epithelial cell population

Abstract: Compromised regenerative capacity of lung epithelial cells can lead to cellular senescence, which may precipitate fibrosis. While increased markers of senescence have been reported in idiopathic pulmonary fibrosis (IPF), the origin and identity of these senescent cells remain unclear, and tools to characterize context-specific cellular senescence in human lung are lacking. We observed that the senescent marker p16 is predominantly localized to bronchiolized epithelial structures in scarred regions of IPF and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 81 publications
2
31
0
Order By: Relevance
“…The senescence phenotype of ATII and the lung fibroblast are also abundant in the lungs of IPF patients [ 67 ]. Recent studies have reported that MUC16 expression correlates with the expression of the senescence marker p16 in IPF lung tissue [ 68 ]. Therefore, we speculate that MUC16 may also collaborate with TGF-β1 to induce cell senescence.…”
Section: Discussionmentioning
confidence: 99%
“…The senescence phenotype of ATII and the lung fibroblast are also abundant in the lungs of IPF patients [ 67 ]. Recent studies have reported that MUC16 expression correlates with the expression of the senescence marker p16 in IPF lung tissue [ 68 ]. Therefore, we speculate that MUC16 may also collaborate with TGF-β1 to induce cell senescence.…”
Section: Discussionmentioning
confidence: 99%
“…To further corroborate the localization of CXCL5/6 expression in IPF lungs, we also queried our recently published IPF scRNASeq dataset (Figure 3A) (15). CXCL6 was expressed predominately in goblet cells, ciliated cells, basal cells, club cells, type I cells, and fibroblasts (16). For comparison, we also analyzed CXCL5 gene expression by scRNASeq and found that CXCL5 is expressed in inflammatory cells including macrophages (Figure 3B).…”
Section: Ipfvsctrl_scrnaseq_cxcr6_wilcoxranksumtxt)mentioning
confidence: 96%
“…Immunostaining for senescent markers p16 and p21 have been localized to AEC2 in patients with IPF and non-IPF UIP (44). In a recent study performed in IPF and SSc-ILD lung tissues, p16 was predominantly localized to bronchiolized epithelium lining honeycomb cysts, specifically to KRT17 + basal epithelial cells that also coexpress KRT5 + (14). This finding is different from the reported by other authors (2,27,63), which found senescence markers in KRT5 -/KRT17 + epithelial cells, supporting the difficulty to identify with precision the senescent epithelial cells in fibrotic lungs.…”
Section: The Usual Interstitial Pneumonia (Uip) Patternmentioning
confidence: 99%